The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11606-014-3112-6
|View full text |Cite
|
Sign up to set email alerts
|

Using a Single Item to Measure Burnout in Primary Care Staff: A Psychometric Evaluation

Abstract: BACKGROUND: Burnout affects nearly half of all U.S. nurses and physicians, and has been linked to poor outcomes such as worse patient safety. The most common measure of burnout is the well-validated Maslach Burnout Inventory (MBI). However, the MBI is proprietary and carries licensing fees, posing challenges to routine or repeated assessment. OBJECTIVE: To compare a non-proprietary, single-item burnout measure to a single item from the MBI Emotional Exhaustion (MBI:EE) subscale that has been validated as a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
402
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 430 publications
(456 citation statements)
references
References 41 publications
7
402
1
8
Order By: Relevance
“…However, this single-item measure has been used previously 38 and shows strong correlation with the emotional exhaustion subscale of the Maslach Burnout Inventory. 33 Second, as a crosssectional survey, we cannot make conclusions regarding causation, only association. With subsequent surveys of VA PCPs and staff, we may be able to study how changes in task delegation affect burnout over time.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, this single-item measure has been used previously 38 and shows strong correlation with the emotional exhaustion subscale of the Maslach Burnout Inventory. 33 Second, as a crosssectional survey, we cannot make conclusions regarding causation, only association. With subsequent surveys of VA PCPs and staff, we may be able to study how changes in task delegation affect burnout over time.…”
Section: Discussionmentioning
confidence: 98%
“…This question has been validated previously against the Emotional Exhaustion Subscale of the Maslach Burnout Inven- tory. 26,33,35 Consistent with previous analyses, a score Ն3 was considered burnout. …”
Section: Burnoutmentioning
confidence: 98%
See 1 more Smart Citation
“…Many previous investigations of burnout have used multi-item scales; however, some have suggested that single-item burnout assessments are a valid and reliable substitute for multiquestion surveys. 46,47 The item used in our study was adapted from this previous work 36 and pilot tested with young pediatricians. Third, although previous research has identified that early career physicians are most likely to have dissatisfaction with overall career choice and the highest frequency of work-home conflicts, our study is limited to early career pediatricians; therefore, the generalizability of the 7 by guest on May 12, 2018 http://pediatrics.aappublications.org/ Downloaded from findings to other specialties or career stages remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] The Physician Work Life Study (PWLS), [26] Minimizing Error and Maximizing Outcome (MEMO) study, [27] and Mississippi Workforce Study (MWS) [28] also used the same measure. It has been validated against (the emotional exhaustion subscale of) the "gold standard" Maslach Burnout Inventory (MBI) among 307 Texas medical school graduates, [29] 740 Australian oncology care providers, [30] 5,404 primary care providers/staff at Veterans Affairs hospitals, [31] and our study sample. [32] The item poses the question: "Overall, how would you rate your level of burnout?"…”
Section: Measures and Variables 241 Main Outcomementioning
confidence: 99%